Narrativity and Literariness Affect the Aesthetic Attitude in Text Reading. (January 2023) - Wimmer, Lena; El-Salahi, Layla; Lee, Hon W. J.; Ferguson, Heather J.
We report two pre-registered experiments investigating some of the conditions under which readers focus on aesthetically relevant object properties in text processing. Experiment 1 ( N = 159) tested the role of narrativity, psychological information about textual characters, and readers' identification with them. Participants' focus on aesthetically relevant object properties was stronger after reading a narrative than an expository text. This relationship between participants' focus and narrativity was not affected by information about textual characters, or readers' identification with them. Experiment 2 ( N = 159) tested the role of narrativity, literariness, and readers' perception of literary features. Again, reading a narrative led to a stronger focus on aesthetically relevant object properties than reading an expository text. The effect of literary narratives was meditated by readers' perception of literary features. In sum, narrativity and literariness, but not information about characters or identification with them affect the degree to which readers focus on aesthetically relevant object properties.